TRADISI MENGHIDUPKAN MALAM NISHFU SYA’BAN PADA KALANGAN MAHASISWA DI KABUPATEN JEMBER (STUDI KRITIK SANAD, MATAN DAN LIVING SUNNAH) - Arbain Nurdin (Pascasarjana UIN ANTASARI Banjarmasin, 2017)
Hadits is the second source of law after the Qur'an, many values or teachings express or implied in the hadits. Among them are the hadith about nishfu Sya’ban narrated by Ibnu Majah. In this paper discussed three aspects namely the power of hadits sanad, the meaning of hadits and actualization of the hadits in the midst of society (Living sunnah). Based on the results of the research, it is found that this hadits is weak because there are among the narrators who are considered to have hadits critics as counterfeiters of hadits. While matan hadits implicitly does not conflict with syari’ah of Islam. And the practices that exist in this hadits still live in the midst of society (students) to this day.